Addressing Maternal Perceived Fears in Supervising Children's Mobility - Nirma Yossa (International Journal of Science and Society, 2023)
Children's independent mobility positively impacts their physical and mental well-being. However, parents' concerns regarding neighbourhood safety often restrict the capability of children to explore their surroundings independently. Our study of various parenting methods for supporting children's everyday use of public space is based on maternal perception of fears and the subsequent impact of those fears on children's limited exposure to spatial mobility. The study employs a qualitative retrospective approach to interview mothers in the Jakarta Metropolitan Area. We selected mothers with an argument that the impact of maternal figures on children's mobility is more significant than that of fathers. The research suggests that mobility experienced by mothers increases their perceived fears resulting in parenting practices that tend to discourage children from independently navigating public spaces. This study demonstrates that a significant reduction in women's ability to have independent mobility throughout their life course may affect their parenting methods in introducing spatial knowledge to children.